Analysis of Tax Sanction Factors in Increasing Land and Building Tax Compliance in Banjarwaringin Village, Salopa District, Tasikmalaya Regency - Anton Bahrul Alam; Eet Saeful Hidayat; Etih Henriyani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract Based on initial observations, tax sanctions in improving compliance with land and building taxes in Banjarwaringin Village, Salopa District, Tasikmalaya Regency are still not optimal. This is evident from the presence of problem indicators, namely: the non-implementation of social and economic sanctions. This study aims to determine how tax sanction factors contribute to the improvement of compliance with land and building taxes in Banjarwaringin Village, Salopa District, Tasikmalaya Regency. This research uses qualitative methods with data collection techniques such as interviews, documentation, and observation. There were 7 informants involved in this research. Based on the research results, it can be concluded that tax sanctions contribute to the improvement of compliance with land and building taxes in Banjarwaringin Village, Salopa District, Tasikmalaya Regency, quite well. There is an indicator that is still not optimal, which is the absence of an agreement on social sanctions and economic sanctions. Keywords: Tax Sanctions, Land and Buildings, Improvement